Provider caring and structuring treatment information to improve cancer patients' recall: Does it help?. Issue 1 (January 2020) - Lehmann, Vicky; Labrie, Nanon H.M.; van Weert, Julia C.M.; van Dulmen, Sandra; de Haes, Hanneke J.C.J.M.; Kersten, Marie José; Pieterse, Arwen H.; Smets, Ellen M.A.
Highlights: Increased provider caring enhances trust. Higher trust may cause (young) patients to overly rely on providers and recall less. Recall of medical information is lower among older people. Structuring information did not enhance information recall. Abstract: Objectives: Patient recall of medical information is usually poor. Healthcare providers can employ affect-oriented (i.e., showing care) or cognition-oriented communication styles (i.e., structuring information) to enhance recall, but research evidence is limited especially among clinical and/or older patient populations. This video-vignette study manipulated provider caring and information structuring to examine effects on recall and trust among cancer patients/survivors. Methods: In an online survey, 148 participants ( M age  = 62) were randomized to one of four video conditions in a two (standard communication vs. enhanced caring) by two (standard vs. enhanced structuring) design, and completed measures of active recall, recognition, and trust. Results: Increased caring or structuring did not enhance active recall or recognition, instead both were higher among younger, female, or highly educated participants. The caring condition induced higher perceived trust in the provider within the whole sample, but trust was significantly correlated with decreased recall ( r  = −.268) among younger participants. Conclusions: Provider caring can strengthen the patient-provider relationship by enhancing trust. Yet, increased trust may impair recall among younger patients. Structuring treatment information did not enhance recall and recognition, but additional research is needed. Practice implications: Providers may use additional ways of structuring/organizing information to help enhance recall (e.g., written information).